Secondary agriculture teachers' knowledge, beliefs and, teaching practices of climate change. Issue 1 (1st January 2020) - Wang, Hui-Hui; Bhattacharya, Devarati; Nelson, Bryanna J.
ABSTRACT: Purpose: Global climate change (GCC) impacts agriculture through food production. Promoting the understanding about GCC among agricultural educators is imperative. While substantive research exists for the knowledge, conceptions, and beliefs of science teachers, few studies focus on agriculture educators. This research investigates the foundational state of secondary agricultural teachers' knowledge, practices, and beliefs about GCC. Design/methodology/approach: In this quantitative study, we used a 22-item survey to capture secondary agriculture teachers' conceptions, beliefs, and practices about GCC. Total 258 secondary agriculture teachers from fourteen states completed the survey. Data was analyzed using descriptive statistics. Findings: Overall, secondary agriculture teachers have a strong understanding about the basic science concepts that constitute the understanding for GCC. However, they are challenged in understanding data that forms the evidence for GCC, and whether this phenomenon is anthropogenic or natural, or both. Their teaching practices about addressing the content of GCC are diverse from spending a dedicated amount of time to none at all in their classrooms. Practical implications: Information acquired will be used to support the agricultural educators needs for resources specifically designed and aligned for the GCC content relevant to agriculture. Theoretical implications: This research informs the field of climate literacy and education through contributing an empirical assessment of one of the underserved population groups – teachers of agricultural education. Originality/value: Very few empirical studies were available for teachers of agriculture, hence this study served as an exploratory foundational work towards future research efforts.